Research progress of endogenous hematoma absorption after intracerebral hemorrhage - Fu, Peijie; Zhang, Manqing; Wu, Moxin; Zhou, Weixin; Yin, Xiaoping; Chen, Zhiying; Dan, Chuanjun (Frontiers in Neurology, 2023)
Nontraumatic intraparenchymal brain haemorrhage is referred to as intracerebral haemorrhage (ICH). Although ICH is associated with a high rate of disability and case fatality, active intervention can significantly lower the rate of severe disability. Studies have shown that the speed of haematoma clearance after ICH determines the patient prognosis. Following ICH, depending on the haematoma volume and mass effect, either surgical- or medication-only conservative treatment is chosen. The goal of promoting endogenous haematoma absorption is more relevant because surgery is only appropriate for a small percentage of patients, and open surgery can cause additional trauma to patients. The primary method of removing haematoma after ICH in the future will involve understanding how to produce and manage macrophage/microglial endogenous phagocytic haematomas. Therefore, it is necessary to elucidate the regulatory mechanisms and key targets for clinical purposes.